2014
DOI: 10.1101/cshperspect.a016634
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism and Regulation of Meiotic Recombination Initiation

Abstract: Meiotic recombination involves the formation and repair of programmed DNA double-strand breaks (DSBs) catalyzed by the conserved Spo11 protein. This review summarizes recent studies pertaining to the formation of meiotic DSBs, including the mechanism of DNA cleavage by Spo11, proteins required for break formation, and mechanisms that control the location, timing, and number of DSBs. Where appropriate, findings in different organisms are discussed to highlight evolutionary conservation or divergence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
468
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 394 publications
(474 citation statements)
references
References 236 publications
6
468
0
Order By: Relevance
“…There were no alterations in the pH2AX staining pattern in the E2F1 −/− ‐testis at P40 compared with E2F1 +/+ , which indicated that increased DNA damage was not the source of the spermatocyte apoptosis. In addition, this shows that the initial meiotic DSB formation occurred normally, as impaired DSB formation commonly leads to a decreased pH2AX staining in the spermatocytes (Hoja et al ., 2004; Lam & Keeney, 2014). This suggested that despite having high E2F1 expression levels in the cell types undergoing meiotic DSB formation, E2f1 did not contribute to this process.…”
Section: Discussionmentioning
confidence: 99%
“…There were no alterations in the pH2AX staining pattern in the E2F1 −/− ‐testis at P40 compared with E2F1 +/+ , which indicated that increased DNA damage was not the source of the spermatocyte apoptosis. In addition, this shows that the initial meiotic DSB formation occurred normally, as impaired DSB formation commonly leads to a decreased pH2AX staining in the spermatocytes (Hoja et al ., 2004; Lam & Keeney, 2014). This suggested that despite having high E2F1 expression levels in the cell types undergoing meiotic DSB formation, E2f1 did not contribute to this process.…”
Section: Discussionmentioning
confidence: 99%
“…1) (see Mehta and Haber 2014). DSBR in meiotic recombination is initiated by the introduction of a large number of programmed DSBs catalyzed by the ScSpo11 protein (see Keeney et al 1997;Lam and Keeney 2015). In mouse and human cells, these programmed DSBs number in the several hundred (Kolas et al 2005;Lenzi et al 2005).…”
Section: Homologous Recombinationmentioning
confidence: 99%
“…They arise during replication fork collapse or exposure to ionizing radiation, reactive oxygen species (ROS), or genotoxic chemicals (Sutherland et al, 2000;Costanzo et al, 2001;Pommier et al, 2003;Mahaney et al, 2009). DSBs are also enzymatically generated intermediates in meiotic recombination, V(D)J, and class switch recombination as well as yeast mating-type switching (Gapud & Sleckman, 2011;Haber, 2012;Xu et al, 2012;Lam & Keeney, 2015). Double-strand breaks can be repaired by different pathways.…”
Section: Introductionmentioning
confidence: 99%